The Role of Character Education in Developing Students' Social-Emotional Competence - Herman Herman; Burhanuddin Burhanuddin (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to explore and analyze the role of character education in developing students' social-emotional competencies at the elementary and secondary school levels. In an increasingly complex educational context where cognitive abilities alone are insufficient to prepare students for social challenges, character education becomes increasingly relevant. Using a qualitative approach, data were collected through in-depth interviews with teachers, students, and parents, as well as direct observation of the implementation of character education programs in schools. The results indicate that character education integrated into the curriculum, extracurricular activities, and school culture has successfully improved students' social skills such as empathy, cooperation, and self-control. Programs involving parents and the community also strengthen the application of character values in students' daily lives. Furthermore, challenges in implementing character education, such as a lack of teacher understanding and limited resources, were also identified as factors that need attention. This study confirms that character education plays a role in shaping individuals who excel not only academically but also possess strong character and good social skills. Therefore, this study recommends the need to strengthen character education programs in schools and closer collaboration between schools, parents, and the community to create a holistic and sustainable learning environment.